2021
DOI: 10.1093/jac/dkab233
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment of liposomal amphotericin B and isavuconazole is synergistic in treating experimental mucormycosis

Abstract: Objectives Liposomal amphotericin B (L-AMB) and isavuconazonium sulphate are commonly used antifungal drugs to treat mucormycosis. However, the efficacy of combination therapy of L-AMB/isavuconazonium sulphate versus monotherapy is unknown. We used an immunosuppressed mouse model of pulmonary mucormycosis to compare the efficacy of L-AMB/isavuconazonium sulphate versus either drug alone. Methods Neutropenic mice were intratra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Of note, isavuconazole has good central nervous system penetration [31] . A study by Gebremariam et al, 2021 found combination therapy of liposomal amphotericin B and isavuconazole, the dual antifungal treatment used in this report, had greater reduction in fungal burden of mucormycosis compared to monotherapy [49] . The patient presented here was able to tolerate dual-antifungal treatment and could not undergo surgical debridement.…”
Section: Discussionsupporting
confidence: 48%
“…Of note, isavuconazole has good central nervous system penetration [31] . A study by Gebremariam et al, 2021 found combination therapy of liposomal amphotericin B and isavuconazole, the dual antifungal treatment used in this report, had greater reduction in fungal burden of mucormycosis compared to monotherapy [49] . The patient presented here was able to tolerate dual-antifungal treatment and could not undergo surgical debridement.…”
Section: Discussionsupporting
confidence: 48%
“…Azoles like isavuconazole and posaconazole oral suspensions are also used in first-line treatment, while terbinafine and echinocandins are not effective against mucormycosis ( 4 ). Ibrahim et al demonstrated the superiority of L-AMB/isavuconazonium sulfate combination over either drug alone in treating murine mucormycosis, however, whether this finding could be transformed into humans warrants further investigation ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the combination is at least expected to reduce the therapeutic doses so that adverse events can be minimized. Some recent animal models have described the synergistic role of triazoles and polyenes [ 36 , 37 ]. The first murine model that described a better survival rate with low dose AMB (0.3 mg/kg/day) and posaconazole combination compared to monotherapy in immunosuppressed mice with disseminated disease.…”
Section: Methodsmentioning
confidence: 99%